The CO2-binding capacity of synthetic anhydrous and hydrates: Validation of a test method based on the instantaneous reaction rate. (September 2020) - Boumaaza, Mouna; Huet, Bruno; Turcry, Philippe; Aït-Mokhtar, Abdelkarim
Abstract: In the present work, a new experimental setup is designed and validated to characterize the CO2 -binding capacity of cementitious materials based on their instantaneous rate of CO2 uptake. An experimental investigation is carried out on synthetized anhydrous (C3 S, C2 S, C3 A) and hydrates (CH, C-S-H, AFt) exposed to ambient CO2 concentration at three different relative humidity (RH) levels. The BET surface area and the density are determined before and after exposure to natural carbonation. Results show that the CO2 – binding capacity and rate increases highly with the RH. The instantaneous binding rate of the materials ranges from 10 −6 to 5.10 −10 gco2 .gpowder −1 .s −1 . The highest degree of carbonation is found for ettringite powder (DoC = 45%). C2 S and C3 A are only slightly carbonated (DoC = 3%), while significant carbonation of C3 S is observed only at 93% RH (DoC = 14%). A good (R 2  = 0.94) agreement between the results determined using the new test method and thermogravimetric analysis (TGA) is noticed.